2010
DOI: 10.1111/j.1475-4983.2010.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

The genus Hispanomeryx (Mammalia, Ruminantia, Moschidae) and its bearing on musk deer phylogeny and systematics

Abstract: We update the systematics and comparative anatomy of the genus Hispanomeryx Morales, Moyà-Solà and Soria, 1981 through the description of a new and abundant fossil material from the middle Miocene localities of Toril-3, Manchones-1 and Manchones-2, Zaragoza Province, Spain. Hispanomeryx was only known by dental remains, mainly mandibles and lower teeth, and very scarce postcranial material; the fossil sample studied here includes cranial, mandibular, dental and postcranial remains, and it allows us to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 33 publications
4
66
0
Order By: Relevance
“…The latter are put into a ''family indet.'' category rather than in the usual family Moschidae, since no relevant morphological characteristics really confirm this assignment (Sánchez et al 2010). Carnivores are represented by at least 13 species in 5 families ( Fig.…”
Section: Composition Of the Faunamentioning
confidence: 90%
“…The latter are put into a ''family indet.'' category rather than in the usual family Moschidae, since no relevant morphological characteristics really confirm this assignment (Sánchez et al 2010). Carnivores are represented by at least 13 species in 5 families ( Fig.…”
Section: Composition Of the Faunamentioning
confidence: 90%
“…They have been considered to be the sister group of Cervidae, Cervidae + Antilocapridae, Cervidae + Bovidae, Bovidae, or all other pecorans (Janis and Scott, 1987;Hernández-Fernández and Vrba, 2005;Vislobokova and Lavrov, 2009;Prikhod'ko and Zvychainaya, 2011). However, recent studies have confirmed Moschidae as the sister group of Bovidae, based on both morphological and molecular methods (Hassanin and Douzery, 2003;Sánchez et al, 2009Sánchez et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In Mongolia, the most ancient Pecora date from the early Oligocene (Vislobokova, 1997;Vislobokova and Daxner-Höck, 2002). Most of these have been tentatively included in the Moschidae (Prothero, 2007); however, recently these attributions have been debated, many researchers have excluded them from Moschidae (Vislobokova, 2007;Vislobokova and Lavrov, 2009;Sánchez et al, 2010;Costeur, 2011), and only two Miocene genera, Micromeryx and Hispanomeryx, are generally regarded as belonging to Moschidae. They share cranial, dental, and postcranial synapomorphies with the extant Moschus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations